Analisis Swot Perencanaan Sistem Informasi Sekolah Musik (Studi Kasus: Majestic Symphony Music School) - Kanggep, Kanggep Andrijana Kusuma; Naufal, Alman; Ratna Juwita Sari, Deassy; Dwicahya Supriatman, Rian; Agung Suburdjati, Bacilius; Maulani, Shanti (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
The information system in a music school business will be crucial in driving the success and progress of the company. Where customer satisfaction can be achieved when the right strategy can be realized in achieving organizational goals. So it is deemed necessary to have an information system to increase business competitiveness for a music school. In information system planning, it is very necessary to use SWOT analysis to get a company's view regarding strengths, weaknesses, opportunities and threats. Which is used to be able to see more comprehensively for decision making purposes. The research carried out aims to analyze external and internal factors. External factors influence opportunities and threats. Factors that occur outside the company that will influence decision making in the company and internal factors which include strengths and weaknesses. In this research, the author made observations at one of the music schools to obtain data, documents, and conducted interviews with business people as sources of information needed by the author. The final results of this research are the SO Strategy (strengths opportunities), the ST Strategy (strengths threats), the WO Strategy (weaknesses opportunities) and the WT Strategy (weaknesses threats). SWOT analysis in the design of an Information system will be very helpful in making decisions on the design of Information Systems and Information Technology in the future for music schools. The suggestion from this research is that the results of the SWOT analysis are only the first step in designing a business strategy. And what will really influence the success of achieving company goals is the next step in determining company decisions regarding Information Systems and Information Technology.